Shock requiring thoracotomy after penetrating thoracic trauma: A case report - Koçkara, Elif; Akça, Hatice Şeyma; Algın, Abdullah; Özdemir, Serdar; Eroğlu, Serkan Emre (Journal of Surgery and Medicine, 2020)
Thoracic trauma is one of the leading causes of 25-50% of all traumatic injuries and death in the entire population. The main problem in thoracic traumas is the disruption of respiratory and hemodynamic functions. We aimed to investigate emergency thoracotomy performed in thoracic injury and its effect on patient mortality. In this case, we examined the time from the arrival of a 41-year-old woman with penetrating multiple injuries to the thorax to the decision to perform an emergency thoracotomy. Although the shock approach and resuscitation protocols were properly applied, an emergency thoracotomy was decided on, since there was no improvement in the patient’s clinical condition and active bleeding was observed in FAST ultrasonography. The patient, whose vital values improved after thoracotomy, was discharged from the hospital after 1 week of intensive care and service follow-up. It should not be forgotten that performing an emergency thoracotomy in intrathoracic penetrating injuries is a key point in the patient’s survival.